1962
DOI: 10.1029/jz067i013p05243
|View full text |Cite
|
Sign up to set email alerts
|

Long-period love waves in a heterogeneous, spherical Earth

Abstract: Abslrnct. Periods of torsional eigenvibrations have been computed for heterogeneous spheres corresponding to a variety of earth models, and the periods of oscillation are used to calculate phase and group velocities for the fundamental and first higher modes of Love waves. A comparison is made between velocities computed for different spherical models and for equivalent ffat cart h structures. The cornpari8on shows (1) that the effect of sphericity is more complicated for fundamental mode Love wa'\·es than for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1963
1963
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Sutton, Ewing & Major (i960) find results similar to those obtained by Dorman for surface waves travelling across the North Pacific. Comparable results have been obtained with Love wave dispersion curves by Sykes, Landisman & Saito (1962) and Kovach & Anderson (1962). Takeuchi et al (1962) find that the Lehmann model fits su propagation across continents.…”
Section: S Eismic E V Id E N C E Of T H E D E E P S T R U C T U R E Of C O N Tin En T Ssupporting
confidence: 53%
“…Sutton, Ewing & Major (i960) find results similar to those obtained by Dorman for surface waves travelling across the North Pacific. Comparable results have been obtained with Love wave dispersion curves by Sykes, Landisman & Saito (1962) and Kovach & Anderson (1962). Takeuchi et al (1962) find that the Lehmann model fits su propagation across continents.…”
Section: S Eismic E V Id E N C E Of T H E D E E P S T R U C T U R E Of C O N Tin En T Ssupporting
confidence: 53%
“…-Sykes et al [1962.] sSated tha• oceanic Rayleigh-and Lovewave velocities -in the period range of 30 to 150 seconds and 10 bo 800 seconds, respectively, can be satisfied by their case 122 model. Kovach and Anderson [1962], however, concluded that no single proposed earth model was completely satisfactory in explaining •he Love-wave data over a wide period range. Anderson and Harkrider [1962] pointed out that model 8099 gave a discrepancy between computed and observed oceanic Rayleigh-wave phase velocities for data in the period range of 250 to 350 seconds, and concluded that it may be necessary to call on anisotropy to explain these differences.…”
Section: The Question Of Anisotropymentioning
confidence: 99%
“…For the intermediate periods, there have been many measurements of phase and group velocities of Love and Rayleigh waves (SatS, 1958;Nafe and Brune, 1960;Brune, Ewing and Kuo, 1961;Brune, Benioff and Ewing, 1961;Ben-Menahem and ToksSz, 1962;B~th and Arroyo, 1962;Matumoto and Sat6, 1962). Most of the observational data, however, show some scatter, and various measurements differ by as much as, and occasionally more than, one per cent of the measured value (Kovach and Anderson, 1962). Part of this variation may be due to the path differences and lateral variations in the structure.…”
Section: Introductionmentioning
confidence: 97%